A novel α-(8-quinolinyloxy) monosubstituted zinc phthalocyanine nanosuspension for potential enhanced photodynamic therapy. (1st November 2020) - Fang, Xiaqin; Xie, An; Song, Hui; Jiang, Dong; Li, He; Wang, Zhiqiang; Tan, Xiaochuan; Zhang, Yujia; Wang, Aiping; Zheng, Wensheng
Abstract: Objective: To prepare α-(8-quinolinyloxy) monosubstituted phthalocyanine zinc nanosuspension (ZnPc-NS) for photodynamic therapy by intravenous administration. Methods: The formulation and preparation technology of ZnPc-NS were assessed by particle size using the precipitation-high pressure homogenization method. The efficacy of ZnPc-NS was evaluated based on particle size, zeta potential, sedimentation ratio, TEM imaging, stability assessment, photodynamic activity and safety. Results and discussion: The content, average particle size, polydispersity and photodegradation constant of ZnPc-NS were 0.2 mg/ml, 219.7 ± 7.41 nm, 0.19 ± 0.02 and 0.006, respectively. The photosensitization rate of singlet oxygen ( 1 O2 ) of the ZnPc-NS was three times higher than that of the ZnPc DMF solution. ZnPc-NS exhibited optimal antitumor activity in HepG2 cells under light exposure and low photo- and non-light-associated toxicity in HELFX cells. In addition, low hemolysis and vascular stimulation were evident in the experiments performed. Conclusion: The ZnPc-NS exhibited optimal stability, faster photosensitization rate of 1 O2, and optimal antitumor activity and safety than the ZnPc DMF solution, which could provide potential support for further research and development.